Analisa Model Strategi Korporasi dalam Penetrasi Perilaku Pembelian pada Industri Roti PT. Hikmat Penuh Berkat (WAKTU: Jurnal Teknik UNIPA, 2026)
Larrita Bakery has become a very popular company in Surabaya. It is certainly a pioneer among food companies that cater to all segments of society. PT Hikmat Penuh Berkat is the owner of this brand, which is supported by approximately 41 outlets within the city. The purpose of this study is to examine the modeling of corporate strategy aspects, including: the influence of market segmentation, product innovation, competency development, expansion, pricing strategy, branding marketing, operational efficiency, sustainability, and agility on purchasing behavior. The results of the data analysis show that not all Corporate Strategy attributes influence Purchasing Behavior. The only attributes that have an influence are Market Segmentation (P=0.007), Product Innovation (P=0.018), Competency Development (P=0.033), and Agility (P=0.016).